Dose reduction of the new generation biologics (IL-17 and IL-23 inhibitors) in psoriasis: study protocol for an international, pragmatic, multicenter, randomized, controlled, non-inferiority study—the BeNeBio study - Lara S. van der Schoot; Juul M. P. A. van den Reek; Lynda Grine; Lisa Schots; Wietske Kievit; Jo L. W. Lambert; Elke M. G. J. de Jong (Trials, 2021)
Abstract Background Psoriasis is a chronic immune-mediated inflammatory skin disease for which biologics are effective treatments. Dose reduction (DR) of the first generation biologics seems a promising way for more efficient use of expensive biologics. A substantial part of patients on tumor necrosis factor (TNF)-alfa inhibitors and ustekinumab could successfully lower their dose, after following a tightly controlled DR strategy. The objective of this study is to assess whether controlled DR of interleukin (IL)-17 and IL-23 inhibitors in psoriasis patients with low disease activity is non-inferior (NI) to usual care (UC). Methods This is an international, prospective, multicenter, pragmatic, randomized, non-inferiority trial. A total of 244 patients with stable low disease activity (Psoriasis Area and Severity Index (PASI) ≤ 5) for at least 6 months and using secukinumab, ixekizumab, brodalumab, guselkumab, risankizumab, or tildrakizumab in the standard dose, together with stable low disease activity, defined as a PASI ≤ 5 and Dermatology Life Quality Index (DLQI) ≤ 5 at the moment of inclusion, will be randomized 2:1 to DR or UC. In the DR group, dosing intervals will be prolonged stepwise to achieve 66% and 50% of the original dose. Disease activity is monitored every 3 months by PASI and DLQI. In case of disease flare (i.e., PASI and/or DLQI increase), treatment is adjusted to the previous effective dose. The primary outcome is the incidence proportion of persistent flares (PASI > 5 for ≥ 3 months), which will be compared between arms. Secondary outcomes include proportion of patients with successful DR, (course of) PASI and DLQI, serious adverse events (SAEs), health-related quality of life, costs, and pharmacokinetic profile. Outcomes of DR will be compared to UC. Discussion With this study, we aim to assess whether DR of IL-17 and IL-23 inhibiting biologics can be achieved for psoriasis patients with low disease activity, without losing disease control. Reducing the dose may lead to more efficient use of biologics. Trial registration ClinicalTrials.gov NCT04340076 . Registered on April 9 2020.